The Essence of the Upanishad in T. S. Eliot’s Poems and Plays - Bhatta, Damaru Chandra (Literary Studies, 2021)
This paper attempts to explore the essence of the principal Upanishads of the Hindu philosophy in T. S. Eliot’s selected seminal poems and plays. The principal Upanishads are the Ishavasya, Kena, Katha, Prashna, Mundaka, Mandukya, Taittiriya, Aitareya, Chhandogya, Brihadaranyaka and Shvetashvatara. The famous poems are “Ash-Wednesday” and Four Quartets, and the famous plays are Murder in the Cathedral, The Family Reunion, and The Cocktail Party under scrutiny in this paper. The essence of the principal eleven Upanishads is that Brahman is source of all creations including the human beings, who get results according to their karma and are born again and again until they get moksha (liberation) through the self-realization of Brahman; therefore, our goal should be to attain moksha or Brahman, only through which we can experience perpetual peace and unbound bliss. Likewise, Eliot suggests that we should attempt to go back to our “Home” (Brahman, also a symbol of peace and bliss), for which we must attempt several times until we become qualified through the non-dual knowledge of “the still point” (Brahman) and its self-realization along with the spiritual practices of renunciation and asceticism. The practice of unattached action done without the hope of its fruit (nishkam karma) and unselfish devotion (Bhakti) are secondary paths to attain liberation. Since the path of spiritual knowledge can make us realize Brahman immediately, Eliot prefers this path of knowledge to the progressive or indirect paths of action and devotion. Thus, his texts reflect the essence of the Upanishads. The significance of this paper within the context of existing scholarship lies in its introduction to the new knowledge that Eliot’s poems and plays could be extensively interpreted by finding the essence of the Upanishads in his texts. Practically, the knowledge of the essence of the Upanishads can help us know the mystery of life and death, and Atman and Brahman, and get liberation from all kinds of suffering and misery, and the cycle of life and death as well before death.